SH_OBERGERICHT 67/2012/3 vom 19. Dezember 2014 - Sh Obergericht (2014)
Art. 76 und Art. 77 Abs. 1 BauG; § 7 Abs. 1 BauV; Art. 46 Satz 1 VRG; Art. 8 Abs. 1, Art. 11, Art. 12 und Art. 13 BGO/Siblingen. | Mehrwertbeiträge; Ausbau einer Quartiererschliessungsstrasse